2007
DOI: 10.1016/j.juro.2007.03.031
|View full text |Cite
|
Sign up to set email alerts
|

The Volume at Which Women Leak First on Urodynamic Testing is Not Associated With Quality of Life, Measures of Urethral Integrity or Surgical Failure

Abstract: Women who demonstrate urodynamic stress incontinence at lower bladder volumes do not report greater bother from incontinence than women who leak at higher volumes, suggesting leakage severity on urodynamics is not an adequate reflection of incontinence related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…This may be seen as a potential limitation; however, this was not the primary aim of the study. In any case, one must bear in mind, as already mentioned, that urinary leaking not always correlates with QoL [36]. Not assessing co-morbid conditions leading to UI may also be seen as a drawback.…”
Section: Discussionmentioning
confidence: 99%
“…This may be seen as a potential limitation; however, this was not the primary aim of the study. In any case, one must bear in mind, as already mentioned, that urinary leaking not always correlates with QoL [36]. Not assessing co-morbid conditions leading to UI may also be seen as a drawback.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies to date demonstrate a weak correlation between symptoms and the results of urodynamic investigation, especially cystometry, in patients with urinary incontinence [3,4,17,18]. This indicates that symptom assessment does not give very sensitive, nor very specific, results with which to define the precise dysfunction of the lower urinary tract.…”
Section: Urodynamic Testingmentioning
confidence: 99%
“…Furthermore, reliable “sub-typing” of urinary incontinence between stress urinary incontinence and detrusor overactivity on the basis of urethral pressures has never been possible. Various studies have shown conflicting results of urethral function tests, such as urethral profiles and closure pressures or leak point pressures in relation to urinary incontinence severity [17,18,29,30]. Contemporary urethral function tests are only very modestly suited to further “sub-categorize” patients with stress (predominant) urinary incontinence for treatment, or to judge the severity of incontinence [34].…”
Section: Urodynamic Testingmentioning
confidence: 99%
“…Traditional measures of urinary incontinence (UI) severity are not well correlated with patient's perceptions of UI severity or satisfaction after continence surgery. 1,2 Previous studies investigated urodynamic parameters as predictors for severity and quality of life (QOL) impact from stress or mixed UI. Measures of sphincteric integrity, valsalva leak point pressures (VLPP), and maximum urethral closure pressures (MUCP) did not correlate with QOL 3,4 although, the amount of urine lost on pad testing correlated moderately with QOL.…”
Section: Introductionmentioning
confidence: 99%
“…However, we previously demonstrated that the bladder volume at which women first demonstrate urodynamic stress incontinence (USI) does not correlate with condition-specific QOL. 2 While the impact of UI on everyday life is not directly related to objective measures of UI severity, 6,7 these discrepancies are poorly understood and may be related to differences in women's abilities to tolerate and adapt to UI symptoms. Personal perceptions of UI symptom severity are affected by several factors, including age, type of UI, and depression.…”
Section: Introductionmentioning
confidence: 99%